Adding sufentanil to ropivacaine in continuous thoracic paravertebral block fails to improve analgesia after video-assisted thoracic surgery: A randomised controlled trial. Issue 10 (October 2018) - Bauer, Christian; Pavlakovic, Isabelle; Mercier, Catherine; Maury, Jean-Michel; Koffel, Catherine; Roy, Pascal; Fellahi, Jean-Luc
Abstract : BACKGROUND: The benefit of adding opioid to a local anaesthetic for continuous thoracic paravertebral analgesia after video-assisted thoracic surgery (VATS) is unclear. OBJECTIVES: To analyse the analgesic efficacy of ropivacaine and sufentanil in combination compared with ropivacaine alone after VATS. DESIGN: A randomised, double-blinded, single-centre clinical trial. SETTING: A tertiary university hospital between March 2010 and April 2014. PATIENTS: Ninety patients were recruited, two were not included leaving 88 randomised into two groups. Eighteen patients were excluded from analysis and 70 completed the study. INTERVENTION: To receive thoracic paravertebral analgesia with either 2 mg ml −1 ropivacaine and 0.25 μg ml −1 sufentanil (ropivacaine + sufentanil group) or 2 mg ml −1 ropivacaine alone (ropivacaine group) for 48 h postoperatively. Infusion rate was set at 0.15 ml kg −1 h −1 in both groups. MAIN OUTCOME MEASURES: The primary endpoint was the mean total amount of self-administered morphine by the patients in each group at 48 h postoperatively. RESULTS: The mean ± SD total amount of self-administered morphine was not significantly different between groups (53.1 ± 27.2 mg in the ropivacaine + sufentanil group vs. 58.8 ± 34.3 mg in the ropivacaine group; P = 0.72). No significant differences were found between the two groups in either pain scores at rest or during movement, in opioid-related adverse reactions, in patient satisfaction or length of hospital stay. CONCLUSION: Adding 0.25 μg ml −1 sufentanil to 2 mg ml −1 ropivacaine in continuous thoracic paravertebral analgesia for VATS did not reduce morphine consumption or pain scores when compared with ropivacaine alone. We cannot recommend its use for routine clinical practice. Further studies analysing different concentrations and infusion rates of sufentanil are needed before a lack of efficacy can be confirmed. TRIAL REGISTRATION: Clinical trial registrations: EudraCT: 2009-014832-38. ClinicalTrials.gov: NCT 01082744. Abstract : Supplemental Digital Content is available in the text